Development of the pectoral, pelvic, dorsal and anal fins in cultured sea bream - Faustino, M. (2014)
The pectoral fin girdle was the first element of the fins to develop in Sparus aurata. By 3·1mm LN (notochord length) the cleithrum was ossified and the cartilaginous caracoid–scapula was present. The fin was fully developed at 11·6 mm LS (standard length) and by 16·0 mm LS most elements of the fin were ossified. The pelvic fins were the last pair to develop and rudiments of these were first detected at 7·9 mm LS. The pelvic fin and girdle were completely formed and ossified at 16·0 mm LS. The development of dorsal and anal fins began at c. 6·5–7·0 mm LS with the formation of 10 cartilaginous dorsal proximal radials and eight cartilaginous ventral proximal radials. The three cartilaginous predorsals(supraneurals) appeared at 7·7 mm LS and the ossification of dorsal and anal proximal and distal radials began, respectively, at 10·5 mm LS and 11·3 mm LS. Ossified structures in the fins were also classified according to their origin, as being either dermal or endochondral. Finally the chronology of appearance of fin structures in S. aurata was compared with that reported for other Sparidae, Engraulidae and Haemulidae.